2006
DOI: 10.1089/apc.2006.20.438
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cell Phone Reminder Calls for Assisting HIV-Infected Adolescents and Young Adults to Adhere to Highly Active Antiretroviral Therapy: A Pilot Study

Abstract: Long-term medication regimen adherence is challenging in all populations, but in the HIVinfected adolescent population the frequency of poverty, homelessness, substance abuse, and mental illness make highly active antiretroviral therapy (HAART) adherence even more challenging. In 2003, we developed a pilot program for HIV-infected adolescents and young adults between the ages of 16 and 24 who were either going to begin a HAART regimen for the first time or begin a new HAART regimen. Participants received a fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 14 publications
2
140
0
Order By: Relevance
“…This study intervention has demonstrated a fairly robust impact when compared to previous interventions for youth living with HIV who demonstrate poor adherence. [10][11][12][13] This study evaluated a very nonadherent population based on low baseline adherence (33% in past month) and very high baseline viral loads …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study intervention has demonstrated a fairly robust impact when compared to previous interventions for youth living with HIV who demonstrate poor adherence. [10][11][12][13] This study evaluated a very nonadherent population based on low baseline adherence (33% in past month) and very high baseline viral loads …”
Section: Discussionmentioning
confidence: 99%
“…8,9 There have been several studies of modestly successful intervention approaches for youth living with HIV who had poor medication adherence including motivational interviewing, 10 directly observed therapy, 11 personalized text message reminders, 12 and cell phone call reminders. 13 More recently, we published an initial randomized controlled trial utilizing cell phone support among nonadherent virologically detectable youth which demonstrated statistically significant improvements in self-reported adherence and reduction in HIV RNA (viral load) at the conclusion of the 24-week intervention and 24 weeks following the completion of the intervention. There were large to medium effect sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons frequently cited by patients missing their appointments are "forgetting the appointment" or "misunderstanding the date or time of the appointment" or "lack of motivation to go to the appointment" [7][8][9][10]. Phone calls, postal, and text reminders have been extensively studied as memory aids to reduce missed appointments [11][12][13]. Mobile phone-based reminders have been found to be effective interventions for missed health care appointments and they increase the rate of attendance among clinical populations.…”
Section: Prior Workmentioning
confidence: 99%
“…While some of them aim to improve care for those with chronic diseases, such as texting reminders to improve adherence to treatment in people with HIV (Puccio et al, 2006), the others aim to promote youth sexual health and disease prevention by downloading applications via smartphones (Levine, 2007). More advanced programs facilitate two-way communications between clients and their healthcare providers, for example, in the self management of diabetes, with clients texting their blood glucose levels and their clinicians reporting back recommendations to alter management (Kim, H-S., Kim, N-C., & Ahn, 2006;Ferrer-Roca, Cardenas, & Diaz-Cardama, 2004).…”
Section: Health Communication and New Information Technologiesmentioning
confidence: 99%